2002
DOI: 10.3346/jkms.2002.17.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Findings of Hepatitis B Infection Based on 1998 National Health and Nutrition Survey in Korea

Abstract: The purpose of this study was to investigate the epidemiological characteristics of hepatitis B virus (HBV) infection in Korea based on the 1998 National Health and Nutrition Survey. Study subjects consisted of 9,771 aged 10 yr or over, who were selected from across Korea using a stratified multistage probability sampling design. The prevalence of hepatitis B surface antigen (HBsAg) was compared by age, sex, residency, household income, education, family history, family size, and frequency of eating out. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 9 publications
5
87
2
1
Order By: Relevance
“…1 The higher prevalence among males in Hawaii is in agreement with recent seroprevalence studies conducted in California and New York [12,15,16]. The nonlinear relationship between age and HBsAg prevalence that was found in this study has also been reported elsewhere, most notably by serologic surveys in Singapore and Korea [36,37]. Significantly lower risk for HBsAg in persons aged 70 years or older might have resulted from spontaneous clearance of HBsAg over time (a 40% cumulative rate of HBsAg seroclearance has been observed among HBV carriers after 25 years) [38].…”
Section: Discussionsupporting
confidence: 92%
“…1 The higher prevalence among males in Hawaii is in agreement with recent seroprevalence studies conducted in California and New York [12,15,16]. The nonlinear relationship between age and HBsAg prevalence that was found in this study has also been reported elsewhere, most notably by serologic surveys in Singapore and Korea [36,37]. Significantly lower risk for HBsAg in persons aged 70 years or older might have resulted from spontaneous clearance of HBsAg over time (a 40% cumulative rate of HBsAg seroclearance has been observed among HBV carriers after 25 years) [38].…”
Section: Discussionsupporting
confidence: 92%
“…However, the reported prevalence of hepatitis B carrier and hepatitis C was about 5% and less than compared the previous era in Korea. 35,36 So it could not be an important confounder in our population study. Second, we had only one measurement of ALT.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have examined the burden of hepatitis infection in South Korea, mostly focusing on hepatitis B, which is regarded as endemic in the country (21). In 1997, the total economic burden of acute hepatitis B was US $120.6 million, which was divided into two components, direct and indirect costs.…”
Section: Discussionmentioning
confidence: 99%